ЕЛЕКТРОМАГНІТНЕ ПОЛЕ ІНДУКТОРІВ ДЛЯ ЛОКАЛЬНОГО ЕЛЕКТРОІМПУЛЬСНОГО ВПЛИВУ НА МЕТАЛЕВІ ВИРОБИ - Васецький, Ю.М.; Кондратенко, І.П. (Інститут електродинаміки НАН України, Київ, 2020)
The mathematical model has been developed to determine of the induced pulsed density current in the conductive sheet and the current parameters of the inductor contour for non-contact electric pulse processing of materials. Based on the calculated data, the prospects of using inductors in the form of current contours for influencing the weld due to the "electroplasticity" effect in the local area are shown. References 7, figures 5.